High mortality risk among women with acromegaly still persists - Găloiu, Simona; Toma, Iustin-Daniel; Tănasie, Denisa Isabella; Bărbulescu, Andreea; Baciu, Ionela; Niculescu, Dan Alexandru; Trifănescu, Raluca Alexandra; Căpăţînă, Cristina; Radian, Şerban; Poiană, Cătălina (Frontiers in Endocrinology, 2024)
Introduction The mortality ratio in patients with acromegaly has improved over the last few decades. We aimed to determine the mortality rate and correlated factors in patients with acromegaly before and after the introduction of national protocols for treatment. In addition, we determined whether there are sex-related differences in mortality of patients with acromegaly. Methods This observational retrospective study included 399 consecutive patients with acromegaly between January 2001–December 2022. Paraclinical data included random growth hormone (GH) and insulin-like growth factor-I (IGF1) levels, maximal pituitary tumor diameter at diagnosis, first visit, and last evaluation. Standardized mortality ratio (SMR) was calculated by dividing the observed and expected mortality rates. Cox regression analysis revealed the independent factors associated with mortality. Results At the last visit, 31.07% (124) of patients were cured, 22.05% (88) had controlled acromegaly with medication, and 45.31% (181) had not controlled acromegaly. During follow-up (13.03 ± 5.65 years, 5216.62 person-years), 89 patients died (0.017%), resulting in an SMR of 1.18 [95% CI 0.95–1.45]. The independent factors associated with mortality were the last IGF1 level/last random GH level, absence of surgery, gonadotropin deficiency, and age. Patients with normal IGF1 after treatment showed an SMR of 0.71, whereas patients with IGF1 ratio > 1 showed SMR=1.51. Patients diagnosed between 1975–2007 and 2008–2022 had SMR = 1.25 [95% CI 0.97–1.58] and SMR = 1.09 [95% CI 0.68–1.65], respectively. In females with acromegaly, SMR was 1.63 [95% CI 1.24–2.11]; 1.76 [95% CI 1.30–2.34] in women diagnosed before 2008 and 1.33 [95% CI 0.69–2.33] in those diagnosed after 2008. Males with acromegaly had a mortality ratio similar to males from the general population (SMR = 0.99, [95% CI 0.66–1.41]). Conclusion Patients diagnosed with acromegaly in the last 15 years had lower mortality rates than those diagnosed before 2008, due to the availability of new medications, primarily somatostatin receptor analogs and to a higher proportion of patients undergoing surgery. Females still have a high mortality ratio owing to older age at diagnosis and higher risk of metabolic complications. Therefore, efforts should be made for early diagnosis of acromegaly in women.